Rescheduling and Reconditioning Policy in the Settlement of Bad Credit - Yusuf Wibisono; Muhamad Mudhofar; Agus Salim (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2023)
Analysiss of Recsheduling And Reconditioning Policy in Settlement of Bad Credit at the Baskara Jaya Yosowilangun Lumajang Savings and Loans Cooperative (KSP). This research is one of the field research where in this research the researcher digs information directly to the Baskara Jaya Yosowilangun Lumajang Savings and Loans Cooperative (KSP). This study used a qualitative approach with the object of research at the Baskara Jaya Yosowilangun Lumajang Savings and Loans Cooperative (KSP). Then supported by a number of literature and some previous research as secondary data. For data collection techniques based on documentation, observation and interviews. Based on the results of observations it was found that the Baskara Jaya Savings and Loans Cooperative (KSP) could run and develop well, although it was not devoid of problems and problems, one of which was the bad credit problem, which was caused by several factors, both internal and external. The management of the Baskara Jaya Savings and Loans Cooperative (KSP) is of course obliged to take policy steps to resolve the problem. Policies undertaken to resolve the problem of bad credit loans, especially with rescheduling and reconditioning policies.